Similarity of heterochromatic regions in the stingless bees (Hymenoptera: Meliponini) revealed by chromosome painting - Lopes, Denilce Meneses; Fernandes, Anderson; Diniz, Debora; Sobrinho Scudeler, Patricia Elda [UNESP]; Foresti, Fausto [UNESP]; Oliveira Campos, Lucio Antonio de (Univ Florence Botany Inst, 2014)
Most Meliponini share a distinctive pattern of heterochromatin distribution in relation to other bees. In general, they present one euchromatic and one heterochromatic chromosome arm, a feature explained by minimum interaction theory, which involved centric fissions followed by heterochromatin addition. In this work, two Meliponini with a distinct pattern of heterochromatin distribution, Tetragonisca fiebrigi and Melipona rufiventris, were analyzed using chromosomal microdissection of the heterochromatin region followed by FISH (fluorescent in situ hybridization). Hybridization revealed FISH signals equivalent to location of the isolated fragment that were widespread over heterochromatic portions of other chromosomes. This result showed that the heterochromatic sequences were very similar among chromosomes in the same species. Cross-hybridization of each probe in M. rufiventris and T. fiebrigi yielded no signals, revealing that both species presented differentiated and non-homologous heterochromatin sequences.
Keywords: Hymenoptera; Meliponini; microdissection; heterochromatin; FISH